Understanding food systems policies for healthy diets in Ethiopia: Opportunities for urban inclusion - Paulos Desalegn; Maryam Rezaei; Shahzoda Alikhanova (ODI Global, 2025)
The Ethiopian Government has recently implemented several initiatives aimed at addressing challenges within their food systems. These challenges lead to high levels of malnutrition and micronutrient deficiency, as well as widespread food insecurity. Despite some progress, the March 2023 national baseline survey still showed high levels of wasting, stunting, and malnutrition. Using Adama City, Ethiopia as a case study, this report aims to understand the impact of the food systems policy environment on access and affordability of healthy diet. The study specifically investigates policy environments conducive to vegetable production, vegetable marketing, and the consumption of a vegetable-rich diet at national and sub-national (i.e. city) levels. Food system policies in Ethiopia are shaped by a combination of historical crises, ideological frameworks, and domestic and international pressures and agendas. While high-profile events and strong advocacy have shaped key food system policy developments, the process remains largely driven by government and donors. Local government, civil society and private sector engagement continues to be marginal, constrained by historical distrust, centralised decision-making and financial limitations.
Keywords: 320; Agriculture & food; Energy; Environment; Climate change